The Belgians to the Front - Fiske, James, 1885-1933; Furman, E. A. (Salt Lake City, UT : Project Gutenberg, 2006)
"The Belgians to the Front" by Colonel James Fiske is a historical account likely written in the early 20th century, during the time of World War I. The story introduces two young Belgian Boy Scouts, Paul Latour and Arthur Waller, who find themselves entangled in the escalating conflict as they gather intelligence about German spies and military movements. Their bravery leads them on exciting and dangerous escapades as they attempt to protect their homeland from invasion, highlighting themes of courage, patriotism, and youthful resourcefulness in the face of war. At the start of the novel, Paul and Arthur engage in a Boy Scout meeting in Liege, where they receive alarming news that war may be imminent. As they depart, Paul expresses unease about a mysterious man they suspect could be a German spy. Their fears are confirmed when they discover important military maps that indicate German plots to invade Belgium. The boys swiftly decide to investigate further while planning to enlist the help of the Belgian military, igniting a series of thrilling adventures that solidify their roles as brave defenders of their country. The opening portion establishes a sense of urgency and foreshadows the impending chaos of war, compelling readers to follow along with the unfolding events. (This is an automatically generated summary.)
Release date is 2006-07-16
E-text prepared by Al Haines
Keywords: World War, 1914-1918 -- Juvenile fiction